Astrocytic Neuroimmunological Roles Interacting with Microglial Cells in Neurodegenerative Diseases - Gotoh, Mari; Miyamoto, Yasunori; Ikeshima-Kataoka, Hiroko (International journal of molecular sciences, 2023)
Both astrocytic and microglial functions have been extensively investigated in healthy subjects and neurodegenerative diseases. For astrocytes, not only various sub-types were identified but phagocytic activity was also clarified recently and is making dramatic progress. In this review paper, we mostly focus on the functional role of astrocytes in the extracellular matrix and on interactions between reactive astrocytes and reactive microglia in normal states and in neurodegenerative diseases, because the authors feel it is necessary to elucidate the mechanisms among activated glial cells in the pathology of neurological diseases in order to pave the way for drug discovery. Finally, we will review cyclic phosphatidic acid (cPA), a naturally occurring phospholipid mediator that induces a variety of biological activities in the brain both in vivo and in vitro. We propose that cPA may serve as a novel therapeutic molecule for the treatment of brain injury and neuroinflammation.